CFD simulation of natural convection and heat transfer in a flat solar thermal collector with fins on the glazing - horizontal case - Adel Laaraba (International Journal of Energetica)
This study is based on a CFD simulation of a flat horizontal solar thermal collector containing fins on its inner face of the glazing. The walls of the solar collector with insulation are considered adiabatic and the rest of the walls are at constant different temperatures. The principal objective of this work is to study the effects of the number of fins that changed from 0 to 30, as well as their length varied from 0 to 0.8 on the air flow and heat transfer characteristics. It has been observed that the heat transfer rate is strongly affected by the number of fins and the length of the fins. The obtained result showed that the increase of the fins reduces the heat loss by convection by 54 %.